Quantity over quality? A European comparison of the changing nature of transitions between non-employment and employment - Werner Eichhorst; Regina Konle-Seidl; Alison Koslowski; Paul Marx (Institute for the Study of Labor (IZA), 2010)
This paper explores the empirical evidence for the claim that non-employed men and women in post-industrial labour markets are more likely to make the transition into employment than has previously been the case. It concludes that whilst the unemployed and the inactive remain distinct groups with regards to transitions into employment, post-industrial labour markets have indeed become more inclusive. Only a few countries saw decreased odds of transition over time for the unemployed, controlling for macro-economic conditions. The picture for the inactive is more mixed cross-nationally. Regarding the question whether an increasingly inclusive labour market is associated with a reduction in job quality, as measured by contract type, the study finds that there is a trend towards more precarious employment for the recently non-employed in some countries such as the Czech Republic, France, Italy and Belgium. In Denmark, Spain, the UK and Hungary, however, there was the opposite trend towards more permanent employment.
Keywords: J41; J62; 330; non-standard employment; fixed-term contracts; transitions